Active Learning Modules for Large Lecture Courses: Implementing the New Essentials - Smith, Hannah R.; Clary-Muronda, Valerie (The Journal of nursing education, 2024)
Competency-based nursing curricula have the potential to shift education in nursing from a knowledge-based approach to teaching that facilitates a deeper understanding of concepts to enhance clinical reasoning. The National Council of State Boards of Nursing (2023) also has shifted its licensing examination, Next Generation NCLEX® (NGN) to better assess competency using the clinical judgment model to provoke student analysis of clinical data. Some of the questions had a higher response rate, suggesting areas of improvement are needed, such as providing an orientation to the platform in the first week of the semester or incorporating these activities as low-stakes assessments and part of the course grade.